2020
DOI: 10.1001/jamainternmed.2019.6390
|View full text |Cite
|
Sign up to set email alerts
|

Post–Acute Kidney Injury Proteinuria and Subsequent Kidney Disease Progression

Abstract: IMPORTANCE Among patients who had acute kidney injury (AKI) during hospitalization, there is a need to improve risk prediction such that those at highest risk for subsequent loss of kidney function are identified for appropriate follow-up.OBJECTIVE To evaluate the association of post-AKI proteinuria with increased risk of future loss of renal function. DESIGN, SETTING, AND PARTICIPANTSThe Assessment, Serial Evaluation, and Subsequent Sequelae in Acute Kidney Injury (ASSESS-AKI) Study was a multicenter prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Two other factors (the number of organ failure and proteinuria) are also affecting both the short-term and long-term all-cause mortality. Many studies reports demonstrated that proteinuria is a well-established biomarker for predicting AKI developing to CKD 40 , 41 . However, proteinuria was also a potentially modifiable risk factor in cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Two other factors (the number of organ failure and proteinuria) are also affecting both the short-term and long-term all-cause mortality. Many studies reports demonstrated that proteinuria is a well-established biomarker for predicting AKI developing to CKD 40 , 41 . However, proteinuria was also a potentially modifiable risk factor in cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal cohort models such as ours, which included diabetes and hypertension as potential confounders, plus the added insult of AKI, it is possible that the small impact attributable to BMI is made negligible by the AKI, and possibly also by the episode of illness leading to hospitalization, as we also did not find evidence of BMI as a risk factor for CKD in this population, with or without AKI. In this same cohort, proteinuria has been identified to increase the risk of kidney disease progression [ 41 ]. Weight loss interventions in those with obesity and CKD have been demonstrated to reduce proteinuria [ 42 ], so there may still be a role for studying obesity interventions after AKI in those with proteinuria, to establish if reducing proteinuria alters CKD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prominent immune complex (IC) deposition at 120 h post-renal I/R in Fcgr2b-/-mice possibly resulted in mononuclear cell infiltrations and inflammatory responses in several organs. In contrast, the only abnormality in WT mice at 120 h post-renal I/R was proteinuria (with normal Scr) due to the incomplete recovery of proximal renal tubules (87). At 120 h postrenal I/R, Fcgr2b-/-mice demonstrated the lupus characteristics as indicated by Scr, anti dsDNA, proteinuria, and glomerular IC deposition.…”
Section: Prominent Nets and Apoptosis In Fcgr2b-/-lupus Mice At 24 H Post-renal I/rmentioning
confidence: 93%